Nematic Fluctuations in Optimally Doped BaFe1.87Co0.13As2 Observed in Photoinduced Reflectivity Change. Issue 3 (3rd January 2020) - Lee, YeongSeon; Kwak, Inho; Lee, Min-Cheol; Seo, Choongwon; Kim, Youngchan; Wolf, Thomas; Noh, TaeWon; Kim, KyungWan
Abstract : The photoinduced reflectivity change of optimally doped BaFe1.87 Co0.13 As2 is investigated. It is observed that the nematic signal in the photoinduced reflectivity change continues to increase as temperature decreases, reflecting its fluctuating nature. However, fluence‐dependent measurements show saturation of the nematic signal at higher pump fluence, a typical behavior of a static order parameter. Temperature‐dependent evolution of the saturation and the characteristic relaxation time of the nematic signal suggest that the nematicity of a spin and/or orbital origin develops at lower temperature on top of the nematicity coupled to the lattice that dominates the higher temperature nematic response. Abstract : Ultrafast photoinduced reflectivity change clearly shows a fluctuating nematic response in optimally doped BaFe1.87 Co0.13 As2 . The nematic signal gets saturated at higher fluence implying that a characteristic energy scale is necessary to destroy the nematic state. Temperature and fluence‐dependent measurements suggest that the nematic response is composed of multiple components possibly of spin and lattice origins.